Emerging Trends in Nanomedicine for Improving Ocular Drug Delivery: Light-Responsive Nanoparticles, Mesoporous Silica Nanoparticles, and Contact Lenses - Rodrigues, Flávia S. C. (2022)
Vision is the most dominant of our senses, and it is crucial in every stage of our lives. Ocular diseases, regardless of whether they cause vision impairment or not, lead to personal and financial hardships. The anatomy and physiology of the eye strongly limit the efficacy of current ocular drug delivery strategies. Nanotechnology has been the ground for the development of powerful strategies in several fields, namely in medicine. This review highlights emerging nanotechnology-based solutions for improving ocular drug delivery and thus the bioavailability and efficacy of drugs. We focus our review on ambitious but promising approaches currently emerging to leverage the efficacy of nanoparticle-based systems in ocular therapy: (i) light-responsive nanoparticles, which enable spatiotemporal control of drug release; (ii) mesoporous silica nanoparticles, which offer high surface area-to-volume ratio, simple surface modification, good biocompatibility, and improved bioavailability; and (iii) contact lenses, which serve as a compliant method of nanoparticles use and as drug delivery systems for the treatment of ocular diseases.